The wall and the gate : Israel, Palestine, and the legal battle for human rights - Sefarad, Mikhaʼel; Johnston, Maya (New York : Metropolitan Books, Henry Holt and Company, 2017)
From renowned human rights lawyer Michael Sfard, an unprecedented exploration of the struggle for human rights in Israel's courts.
Introduction -- The battleground -- Deportations : raising the stakes -- Settlements : banging one's head against the wall of the political -- Torture -- The separation wall -- Unauthorized outposts -- Security and the piccolo -- Conclusion.
Includes bibliographical references and index.
Keywords: Palestinian Arabs -- Civil rights -- West Bank; Palestinian Arabs -- Civil rights -- Gaza Strip; Human rights -- West Bank; Human rights -- Gaza Strip; Law and geography -- West Bank; Law and geography -- Gaza Strip